A Study on Women Oriented Characters in the Works of Shakespeare: Exploring Women's Roles in Shakespearean Tragedies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Shakespeare showed positive attitude toward women in his tragedies like Romeo and Juliet, Hamlet, Macbeth, Othello etc. He showed various aspects of women behavior in his tragedies very intelligently. The women character of Ophelia in Hamlet is the good example of that. She was deployed as victim figure. Hamlet used Ophelia as a tool for revenge throughout the play. She considered herself guilty when Hamlet murdered her father and got mad.Also, in Othello, Shakespeare showed the character of Desdemona very obedient in her disobedient. Desdemona had to suffer a lot due to misunderstandings. Othello considered her betrayal. She loved Othello very much but he lost his trust on her due to virtual circumstances.